A Comparative Analysis of Sharia E-Commerce, Sharia Credit Cards, and Sharia Franchising from the Perspective of Maqashid Al-Sharia - Sulaiman, Dody; Busnetty , Ida (Journal Research of Social Science, Economics, and Management, 2026)
The rapid growth of digital technology has transformed economic activities, creating new opportunities and challenges for Islamic finance in Muslim-majority countries like Indonesia. Sharia-compliant instruments, including sharia e-commerce, sharia credit cards, and sharia franchising, have emerged to facilitate ethical digital transactions in accordance with Islamic law. This study aims to examine and compare these three instruments using the maqashid al-sharia framework to evaluate their compliance, legal validity, and contribution to societal welfare. The research employs a normative legal methodology, combining conceptual analysis, comparative analysis, and maqashid-based assessment. Primary data include DSN-MUI fatwas, Quranic verses, and hadiths, while secondary data encompass classical fiqh texts, contemporary Islamic finance literature, and academic journal articles. Thematic content analysis was conducted to identify contract types, adherence to sharia prohibitions, and the instruments' contributions to the five dimensions of maqashid al-sharia. Findings reveal that all three instruments are permissible (mubah) when contractual pillars are fulfilled and prohibited elements such as riba and gharar are avoided. Each instrument employs combined contracts to manage complex digital transactions effectively. While they strongly support wealth protection (hifzh al-mal) and religious compliance (hifzh al-din), their contributions to intellectual development, family welfare, and social sustainability remain limited. The study concludes that continuous oversight, integration of ethical considerations, and adoption of advanced monitoring technologies are necessary to enhance the effectiveness and societal impact of Islamic digital financial instruments.